Reading the Waves: Continuity and Change in Ocean Lawmaking - Novak, Gregor (Columbia Journal of Environmental Law, 2022)
During the last several decades the ocean has maintained its historically pivotal socio-economic and geopolitical role. Humans rely on the ocean for habitation and nourishment, energy and sanitation, migration and refuge, trade and communication, knowledge and meaninggiving, and the maintenance of global peace and security. Yet many who depend on the ocean are poorly served by what may be called “ocean law.” Moreover, the ocean and its resources are under acute strain through overfishing, the varied consequences of climate change and ocean degradation, sea-level rise, and the risk of marine infectious diseases, among other threats. This Article identifies widely-recognized deficiencies in “ocean law,” traces them to the design of ocean lawmaking, and draws on the latter’s history to point towards a path of democratic reform. Navigators are skilled at “reading the waves,” distilling insights about past and likely future events from ripples on the ocean’s surface. Similarly, this Article samples from the modern history of humanity’s relationship with the ocean to gain insights into continuities, changes, and dynamic elements in contemporary ocean lawmaking. The Article argues that keeping in mind, supporting, and leveraging certain dynamic elements revealed in this lawmaking arena can help democratize ocean lawmaking and accelerate sorely needed reforms in ocean law. Such reforms are needed because contemporary ocean lawmaking has produced ocean law whose main defect is not merely that it is patchy, uncoordinated, and often ineffective but that it is heavily skewed towards powerful actors with vested interests in the status quo. As a result, it has sidelined those who must bear the downstream costs of its lawmaking outcomes and placed at risk the very survival of the ocean ecosystem and those who rely on it. In turn, any reform of ocean lawmaking should give more power and voice to vulnerable coastal communities, victims of human trafficking, refugees, maritime workers, people deriving their livelihood from the marine economy, consumers, the scientific community, indigenous peoples, future generations, and the maritime ecosystem itself.